Polymer solid electrolyte and its manufacturing method
The polymer solid electrolyte with a crosslinking structure and amorphous polymer chains addresses the challenge of low ionic conductivity in conventional polymer solid electrolytes by reducing crystallinity and enhancing lithium ion mobility, achieving performance comparable to liquid electrolytes.
Patent Information
- Application Number
- JP2024553868
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-05-31
- Filing Date
- 2023-05-31
- Publication Date
- 2025-04-16
AI Technical Summary
Conventional polymer solid electrolytes face challenges in achieving improved ionic conductivity due to the high crystallinity of crystalline or semi-crystalline polymers, which limits the mobility of lithium ions.
A polymer solid electrolyte is developed with a crosslinking structure and amorphous polymer chains, formed through the crosslinking of a polymer containing crosslinkable functional groups with a lithium salt and a solvent, followed by a solvent exchange process.
The resulting polymer solid electrolyte exhibits reduced crystallinity, increased ductility and viscosity, and enhanced ionic conductivity, comparable to or exceeding that of conventional liquid electrolytes.
Smart Images

Figure 2025511517000001 
Figure 2025511517000002 
Figure 2025511517000003
Abstract
Description
[Technical field]
[0001] This application claims the benefit of priority based on Korean Patent Application No. 10-2022-0066993 filed on May 31, 2022 and Korean Patent Application No. 10-2023-0070184 filed on May 31, 2023, and incorporates all contents disclosed in the documents of said Korean patent applications as part of this specification.
[0002] The present invention relates to a polymer solid electrolyte and a method for producing the same. [Background technology]
[0003] Lithium secondary batteries that use liquid electrolytes have a structure in which the negative and positive electrodes are separated by a separator, and if the separator is damaged due to deformation or external impact, a short circuit may occur, which may lead to the risk of overheating or explosion, etc. Therefore, the development of a solid electrolyte that can ensure safety in the field of lithium secondary batteries is a very important issue.
[0004] Lithium secondary batteries using solid electrolytes have the advantages of increased battery safety, prevention of electrolyte leakage, improved battery reliability, and ease of manufacturing thin batteries. In addition, because lithium metal can be used for the negative electrode, the energy density can be improved, and it is expected that they will be used in small secondary batteries as well as high-capacity secondary batteries for electric vehicles, and are attracting attention as next-generation batteries.
[0005] Among solid electrolytes, polymeric solid electrolytes can be made from ion-conductive polymer materials, and hybrid materials made from a mixture of polymeric and inorganic materials have also been proposed. The inorganic material can be an inorganic material such as an oxide or sulfide.
[0006] Such conventional polymer solid electrolytes are manufactured through a process of forming a coating film and then drying it at a high temperature. However, the conventional manufacturing technology for polymer solid electrolytes has a limitation in that it is difficult to manufacture a polymer solid electrolyte with improved ion conductivity due to the high crystallinity of a crystalline polymer or a semi-crystalline polymer. That is, the higher the crystallinity of the polymer, the lower the chain mobility of the polymer. As a result, the movement of lithium ions inside the polymer solid electrolyte is restricted, making it difficult to improve the ion conductivity of the polymer solid electrolyte.
[0007] For example, a conventional polymer solid electrolyte can be manufactured by forming a coating film using polyvinyl alcohol (PVA) containing a hydroxyl group, which is a cross-linking functional group, as a polymer, and then performing a high-temperature drying process. Specifically, the PVA is dissolved in water to prepare a PVA aqueous solution, and the PVA aqueous solution is applied to a substrate by solution casting to form a coating film, and the coating film is dried at room temperature or a high temperature to manufacture a polymer solid electrolyte in the form of a PVA film. In this case, high temperature may mean 80°C or higher, which is the glass transition temperature (Tg) of PVA. In the drying process, after water is evaporated, hydrogen bonds are formed between the cross-linking functional groups contained in the PVA, and polymer chain folding occurs due to the hydrogen bonds, resulting in a phenomenon in which the crystallinity of the polymer film is increased. The higher the crystallinity, the more brittle the polymer film is formed. In a polymer film having a high degree of crystallinity and brittleness, the chain mobility of the polymer chain is reduced, and when dissociated ions exist inside the polymer film, the ion mobility is also significantly reduced. As a result, a typical PVA film manufactured by forming a coating film and then drying it at high temperature as described above exhibits physical properties that are not suitable for use as a polymer solid electrolyte for lithium secondary batteries.
[0008] To overcome these limitations of conventional polymer solid electrolytes, a technology has been developed to improve the mobility of polymer chains by adding a plasticizer to a crystalline or semi-crystalline polymer, thereby improving the ionic conductivity of the polymer solid electrolyte. However, when using a plasticizer, it can be difficult to set process conditions because appropriate dispersion and solubility between the polymer and the plasticizer must be ensured. In addition, when a liquid plasticizer is used, the compatibility with the polymer decreases, making it difficult to carry out the manufacturing process of the polymer solid electrolyte.
[0009] Therefore, there is a need to develop a technology that can improve the ionic conductivity of polymer solid electrolytes without the use of separate additives such as plasticizers. [Prior art documents] [Patent documents]
[0010] [Patent Document 1] Chinese Patent No. 112259788 Summary of the Invention [Problem to be solved by the invention]
[0011] An object of the present invention is to provide a polymer solid electrolyte having improved ionic conductivity.
[0012] Another object of the present invention is to provide a method for producing a polymer solid electrolyte having improved ionic conductivity.
[0013] Another object of the present invention is to provide an all-solid-state battery including a solid polymer electrolyte with improved ionic conductivity. [Means for solving the problem]
[0014] In order to achieve the above objectives, The present invention provides a polymer solid electrolyte comprising: a polymer including a cross-linkable functional group; a lithium salt including a first lithium salt and a second lithium salt; and a solvent including a first solvent and a second solvent; the polymer solid electrolyte comprises a cross-linked structure; and an amorphous polymer chain including the cross-linkable functional group, the cross-linked structure including (a) a cross-link between the cross-linkable functional groups, (b) a cross-link between the cross-linkable functional group and the first solvent, and (c) a bond between the cross-linkable functional group and the first lithium salt.
[0015] The present invention also provides a method for producing a polymer solid electrolyte, the method including: (S1) adding a first lithium salt to a solution containing a polymer having a cross-linkable functional group and a first solvent to prepare a polymer solid electrolyte forming solution; (S2) coating the polymer solid electrolyte forming solution on a substrate to form a coating film; (S3) freezing and thawing the coating film to form a cross-linked structure of the polymer having the cross-linkable functional group, the cross-linked structure of the polymer including the first lithium salt and the first solvent to prepare a first polymer solid electrolyte; and (S4) exchanging the first solvent in the first polymer solid electrolyte with a solution containing a second lithium salt and a second solvent to prepare a second polymer solid electrolyte.
[0016] The present invention also provides an all-solid-state battery comprising the polymer solid electrolyte. Effect of the Invention
[0017] The polymer solid electrolyte according to the present invention has a cross-linked structure formed by cross-linking functional groups contained in the polymer and a structure including an amorphous polymer chain, which reduces the crystallinity of the polymer, thereby improving ion conductivity.
[0018] In addition, the polymer solid electrolyte exhibits physical properties such as reduced brittleness and increased ductility and viscosity due to the structural characteristics.
[0019] In addition, the ionic conductivity of the polymer solid electrolyte can be improved by performing solvent exchange with a solvent containing a lithium salt using the polymer solid electrolyte. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0020] The present invention will now be described in further detail to aid in the understanding of the present invention.
[0021] The terms and words used in this specification and the claims should not be interpreted in a limited manner based on their ordinary or dictionary meanings, but should be interpreted in a meaning and concept that corresponds to the technical idea of the present invention, based on the principle that the inventor can appropriately define the concept of the term in order to best describe his / her invention.
[0022] The term "crosslinked structure" as used herein means a structure including a three-dimensional frame formed by polymer chains and an internal space of the frame. The polymer chains may be formed by crosslinking involving crosslinking functional groups contained in the polymer. The crosslinked structure has a three-dimensional shape and is in a form in which the polymer chains are intertwined with each other, and therefore can also be called a three-dimensional network structure.
[0023] Polymer solid electrolyte In one embodiment of the present invention, the polymer solid electrolyte includes a polymer including a cross-linkable functional group; a lithium salt including a first lithium salt and a second lithium salt; and a solvent including a first solvent and a second solvent; the polymer solid electrolyte includes a cross-linked structure; and an amorphous polymer chain including the cross-linkable functional group, and the cross-linked structure can include (a) a cross-link between the cross-linkable functional groups, (b) a cross-link between the cross-linkable functional group and the first solvent, and (c) a bond between the cross-linkable functional group and the first lithium salt.
[0024] In the present invention, the (a) cross-linking bond between the cross-linking functional groups may include a hydrogen bond between the cross-linking functional groups, and for example, the hydrogen bond may be a hydrogen bond between OH-.
[0025] If the cross-linked structure is composed only of cross-links between the (a) cross-linkable functional groups, the polymer solid electrolyte may become crystalline, resulting in a decrease in ionic conductivity.
[0026] However, since the cross-linked structure includes not only the (a) cross-linking between the cross-linking functional groups, but also the (b) cross-linking between the cross-linking functional group and the first solvent, and the (c) bond between the cross-linking functional group and the first lithium salt, the occurrence of crystallinity in the polymer solid electrolyte can be prevented.
[0027] In the present invention, the (b) cross-linking between the cross-linkable functional group and the first solvent may include a hydrogen bond, for example, the hydrogen bond may be a hydrogen bond between OH- and H+, where H+ may be derived from the water solvent.
[0028] The (b) cross-linking between the cross-linkable functional group and the first solvent may refer to hydrogen bonding between the cross-linkable functional group and a portion of the solvent remaining after the freezing and thawing process.
[0029] In addition, the crosslinking between the (b) crosslinkable functional group and the first solvent interferes with the crosslinking between the (a) crosslinkable functional groups, and prevents the crosslinked structure from being composed only of crosslinks between the (a) crosslinkable functional groups, thereby preventing an increase in the crystallinity of the polymer solid electrolyte.
[0030] In the present invention, the bond between the (c) crosslinkable functional group and the first lithium salt may include a bond due to a Lewis acid-base interaction, for example, the bond may be a bond between OH and Li.
[0031] The bond between the (c) cross-linkable functional group and the first lithium salt is a bond based on Lewis acid-base interaction, and may be a bond in the form of a metal-ligand bond.
[0032] In addition, the bond between the (c) cross-linking functional group and the first lithium salt interferes with the cross-linking between the (a) cross-linking functional group and the (b) cross-linking between the cross-linking functional group and the first solvent, and the cross-linked structure is not composed only of the cross-linking between the (a) cross-linking functional group, thereby preventing the occurrence of crystallinity in the polymer solid electrolyte and promoting the formation of amorphous polymer chains. As the amorphous polymer chains are formed, the mobility of the polymer chains is improved, and the hopping effect of the lithium ions is increased, thereby improving the ionic conductivity of the polymer solid electrolyte.
[0033] In the present invention, the amorphous polymer chain can also be formed by a freezing process as described below, and refers to a polymer chain that does not form crystals due to regular folding of the polymer chain and exists in a free state. That is, the amorphous polymer chain may include a polymer that includes a cross-linkable functional group that does not form a bond as in (a), (b), and (c).
[0034] Due to the cross-linked structure, the polymer solid electrolyte is not easily broken or destroyed, and can function as an electrolyte support that stably contains lithium ions.
[0035] In addition, the amorphous polymer chains make the polymer solid electrolyte elastic, minimizing brittleness, which is a property of being easily broken. Also, the polymer chain mobility is excellent, and the mobility of lithium ions within the electrolyte is improved, thereby providing a polymer solid electrolyte with improved ion conductivity.
[0036] In the present invention, the cross-linkable functional group contained in the polymer containing the cross-linkable functional group may have the property of being able to form a cross-linked structure by forming bonds such as those of (a), (b), and (c).
[0037] For example, the cross-linkable functional group may include one or more selected from the group consisting of a hydroxyl group, a carboxyl group, and an amide group.
[0038] In addition, the weight average molecular weight (Mw) of the polymer containing the crosslinkable functional group may be 80,000 g / mol to 130,000 g / mol, specifically, 80,000 g / mol or more, 83,000 g / mol or more, or 85,000 g / mol or more, and 90,000 g / mol or less, 110,000 g / mol or less, or 130,000 g / mol or less. If the weight average molecular weight (Mw) of the polymer containing the crosslinkable functional group is less than 80,000 g / mol, the bond by the crosslinkable functional group may not be formed sufficiently to obtain a crosslinked structure. If the weight average molecular weight (Mw) of the polymer containing the crosslinkable functional group exceeds 130,000 g / mol, the entanglement of the polymer chain increases in the polymer solution used in the manufacturing process, and the solvent penetration rate into the inside of the polymer chain decreases. This may accelerate gelation of the polymer, reduce the solubility of the polymer, and inhibit smooth bonding via cross-linking functional groups, making it difficult to form a cross-linked structure.
[0039] In addition, the polymer containing the cross-linkable functional group may be characterized in that phase separation between the polymer and a solvent is smoothly performed in the polymer solution used in the manufacturing process, and the bonds (a), (b), and (c) are well formed by the cross-linkable functional group contained in the phase-separated polymer upon freezing.
[0040] For example, the polymer containing a cross-linkable functional group may include at least one selected from the group consisting of polyvinyl alcohol (PVA), gelatin, methylcellulose, agar, dextrin, poly(vinyl pyrrolidone), poly(acryl amide), poly(acrylic acid) (PAA), starch-carboxymethyl cellulose, hyaluronic acid-methylcellulose, chitosan, poly(N-isopropylacrylamide), and amino-terminated PEG. Preferably, the polymer having a cross-linkable functional group may be PVA, which can efficiently perform phase separation between the PVA and a solvent upon freezing during the preparation of a polymer solid electrolyte, and can be advantageous in forming a cross-linked structure through the (a), (b), and (c) bonds derived from the cross-linkable functional group of the PVA that is phase-separated from the solvent.
[0041] In the present invention, the first lithium salt is contained in the internal space of the cross-linked structure in a dissociated state, and can improve the ionic conductivity of the polymer solid electrolyte.
[0042] In addition, the first lithium salt forms a bond with the (c) cross-linking functional group and the first lithium salt, thereby preventing the generation of crystallinity in the polymer solid electrolyte and simultaneously promoting the formation of amorphous polymer chains.
[0043] The first lithium salt is selected from the group consisting of (CF3SO2)2NLi (lithium bis(trifluoromethanesulphonyl)imide, LiTFSI), (FSO2)2NLi (lithium bis(fluorosulfonyl)imide, LiFSI), LiNO3, LiOH, LiCl, LiBr, LiI, LiClO4, LiBF4, LiB 10 Cl 10 , LiPF6, LiCF3SO3, LiCF3CO2, LiAsF6, LiSbF6, LiAlCl4, CH3SO3Li, CF3SO3Li, LiSCN, and LiC(CF3SO2)3.
[0044] In the present invention, the molar ratio ([Li] / [G]) of the crosslinkable functional group ([G]) of the polymer containing the crosslinkable functional group and the lithium ([Li]) of the first lithium salt contained in the polymer solid electrolyte may be more than 0.1 and less than 0.5, specifically, more than 0.1, 0.2 or more, or 0.3 or more, and may be 0.4 or less, or less than 0.5. If the molar ratio ([Li] / [G]) is 0.1 or less, the content of the first lithium salt may decrease, and the ionic conductivity of the polymer solid electrolyte may decrease, and if it is 0.5 or more, the content of the polymer containing the crosslinkable functional group may decrease, and the bonds (a), (b), and (c) may not be sufficiently formed, which may increase the crystallinity and decrease the ionic conductivity. If the crosslinkable functional group is a hydroxyl group (OH-), the [G] may be expressed as [OH] or [O].
[0045] In one embodiment of the present invention, the first solvent is contained within a cross-linked structure formed by physical cross-linking of the polymer solid electrolyte, facilitating a solvent exchange process and improving the ionic conductivity of the polymer solid electrolyte.
[0046] The first solvent and the second solvent are distinct from each other and may have different solubilities for the polymer having the cross-linkable functional group.
[0047] The first solvent has high solubility for the polymer containing the cross-linkable functional group and can form a cross-linked structure with the polymer containing the cross-linkable functional group, whereas the second solvent has low solubility for the polymer containing the cross-linkable functional group and has difficulty in forming a cross-linked structure with the polymer containing the cross-linkable functional group.
[0048] The first solvent and the second solvent may be solvents classified as an aqueous electrolyte solution or a non-aqueous electrolyte solution depending on the battery structure.
[0049] The first solvent and the second solvent may be solvents distinguished from each other by a flame-retardant electrolyte.
[0050] The first solvent may be any one selected from the group consisting of water, ethanol, isopropyl alcohol, dimethyl sulfoxide, acetonitrile, NMP, a co-solvent made by mixing water and alcohols, and a co-solvent made by mixing water and dimethyl sulfoxide.
[0051] The boiling point of the first solvent may be 150° C. or less. The boiling point of the first solvent may be lower than the boiling point of the second solvent. If the boiling point of the first solvent exceeds 150° C., hydrogen bonds and Lewis acid-base interactions formed within the polymer may be broken during the process of removing the first solvent, and the mechanical properties of the polymer solid electrolyte may be significantly reduced.
[0052] The first solvent can dissolve the polymer having a cross-linkable functional group and then form a cross-linked structure through a freezing / thawing process. For example, when the first solvent is water, phase separation with the polymer having a cross-linkable functional group can occur significantly during the freezing process, forming an ice phase and a rich phase of the polymer having a cross-linkable functional group.
[0053] The content of the first solvent in the polymer solid electrolyte may be 1 to 1000 ppm. If the content of the first solvent exceeds 1000 ppm, the absorption of the second solvent is inhibited, and the physical properties expected from the second solvent, such as ion conductivity, are reduced.
[0054] The second solvent may include one or more selected from the group consisting of ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), ethylene carbonate (EC), propylene carbonate (PC), vinylene carbonate (VC), diethyl carbonate (DEC), methyl ethyl carbonate (MEC), tetrahydrofuran (THF), 2-methyltetrahydrofuran (2-MeTHF), dioxolane (DOX), dimethoxyethane (DME), diethoxyethane (DEE), γ-butyrolactone (GBL), acetonitrile (AN) and sulfolane, or may include combinations thereof. For example, EC:EMC (1:3), EC:EMC (1:1), EC:DMC:EMC:FEC (3:3:3:1), etc. may be included, but are not limited to these examples.
[0055] The polymer solid electrolyte according to the present invention includes a second lithium salt and a second solvent, so that a polymer solid electrolyte having improved ion conductivity can be provided.
[0056] In general, ionic conductivity can be defined as follows:
[0057] [Formula 1]
number
[0058] In the formula 1, σ is ionic conductivity, n is lithium ion concentration, q is charge, and μ is ionic mobility. As shown in the formula 1, in order to improve the ionic conductivity of the solid electrolyte, it is desirable to increase the lithium ion concentration or ionic mobility. The polymer solid electrolyte including the cross-linked structure and the amorphous polymer chain according to the present invention can improve the ionic mobility. The second lithium salt is further included in the polymer solid electrolyte in order to increase the lithium ion concentration.
[0059] The concentration of the second lithium salt may be 0.5 M to 1.2 M. More specifically, the concentration of the second lithium salt may be 0.5 M or more, 0.6 M or more, 0.7 M or more, 0.8 M or more, 0.9 M or more, or 1.0 M or more, or 1.2 M or less, 1.1 M or less, 1.0 M or less, 0.9 M or less, 0.8 M or less, or 0.7 M or less. If the concentration of the second lithium salt is less than 0.5 M, the ionic conductivity may decrease due to a decrease in the concentration of mobile lithium ions in the electrolyte, and if the concentration of the second lithium salt exceeds 1.2 M, a problem may occur in which the ionic conductivity of the electrolyte decreases due to a decrease in the degree of dissociation caused by the aggregation of lithium ions.
[0060] The second lithium salt not only increases the lithium ion concentration in Formula 1, but also reduces hydrogen bonds between polymer chains through Lewis acid-base action to form an amorphous structure. In fact, the concentration of freely mobile lithium ions may be reduced due to lithium ions participating in the Lewis acid-base reaction, or some lithium ions may react with water to form by-products such as LiOH, thereby reducing the overall concentration of mobile lithium ions. Therefore, compensating for the concentration of lithium ions in the polymer solid electrolyte through the second lithium salt can improve the ionic conductivity of the solid electrolyte. In addition, the second lithium salt can also compensate for the loss of lithium ions that may occur during the process of preparing the solid electrolyte by forming physical cross-links through freezing and thawing processes.
[0061] The second lithium salt is, for example, (CF3SO2)2NLi (lithium bis(trifluoromethanesulphonyl)imide, LiTFSI), (FSO2)2NLi (lithium bis(fluorosulfonyl)imide, LiFSI), LiNO3, LiOH, LiCl, LiBr, LiI, LiClO4, LiBF4, LiB 10 Cl 10 , LiPF6, LiCF3SO3, LiCF3CO2, LiAsF6, LiSbF6, LiAlCl4, CH3SO3Li, CF3SO3Li, LiSCN, and LiC(CF3SO2)3.
[0062] The concentration of the second lithium salt may be 0.5 M to 1.2 M. More specifically, the concentration of the second lithium salt may be 0.5 M or more, 0.6 M or more, 0.7 M or more, 0.8 M or more, 0.9 M or more, or 1.0 M or more, or 1.2 M or less, 1.1 M or less, 1.0 M or less, 0.9 M or less, 0.8 M or less, or 0.7 M or less. If the concentration of the second lithium salt is less than 0.5 M, the ionic conductivity may decrease due to a decrease in the concentration of mobile lithium ions in the electrolyte, and if the concentration of the second lithium salt exceeds 1.2 M, a problem may occur in which the ionic conductivity of the electrolyte decreases due to a decrease in the degree of dissociation caused by the aggregation of lithium ions.
[0063] In the present invention, the polymer solid electrolyte may be in the form of a free-standing film or a coating layer. The free-standing film refers to a film that can maintain a film shape by itself without a separate support at room temperature and pressure. The coating layer refers to a layer obtained by coating on a substrate. When the polymer solid electrolyte is in the form of a coating layer, the coating layer may be in the form of a layer coated on an electrode.
[0064] The free-standing film or coating layer may exhibit elasticity and minimize brittleness, and may have properties as a support that stably contains lithium ions, making it suitable for use as a polymer solid electrolyte.
[0065] In the present invention, the ionic conductivity of the polymer solid electrolyte is 10 -4 It may be S / cm or more.
[0066] The polymer solid electrolyte has low crystallinity and high ionic conductivity due to its structural characteristics including the cross-linked structure as described above. Therefore, despite being a solid electrolyte, it exhibits ionic conductivity at a level equal to or higher than that of conventional liquid electrolytes, thereby improving the performance of all-solid-state batteries.
[0067] Method for producing polymer solid electrolyte A method for preparing a polymer solid electrolyte according to an embodiment of the present invention may include the following steps: (S1) preparing a polymer solid electrolyte forming solution by adding a first lithium salt to a solution including a polymer including a cross-linking functional group and a first solvent; (S2) applying the polymer solid electrolyte forming solution onto a substrate to form a coating film; (S3) freezing and thawing the coating film to form a polymer cross-linked structure including the cross-linkable functional group, the polymer cross-linked structure including the first lithium salt and the first solvent, to prepare a first polymer solid electrolyte; (S4) exchanging the first solvent in the first polymer solid electrolyte with a solution including a second lithium salt and a second solvent to prepare a second polymer solid electrolyte.
[0068] In the method for manufacturing the polymer solid electrolyte, a plasticizer used to reduce the crystallinity of the polymer is not added, and instead, a physical cross-linking of the polymer including a cross-linking functional group is induced, thereby preventing the crystallization of the polymer. In addition, the polymer solid electrolyte according to one embodiment of the present invention in which the crystallization of the polymer is prevented is easy to carry out a solvent exchange process, and a polymer solid electrolyte having improved ion conductivity can be manufactured through the solvent exchange process.
[0069] Hereinafter, each step of the method for preparing a polymer solid electrolyte according to the present invention will be described in detail.
[0070] In one embodiment of the present invention, in the step (S1), a solution for forming a polymer solid electrolyte may be prepared by adding a first lithium salt to a solution including a polymer having a cross-linkable functional group and a first solvent.
[0071] The polymer, the first solvent, and the first lithium salt are as described above.
[0072] The concentration of the polymer solution containing a crosslinkable functional group may be appropriately adjusted in consideration of the degree to which the coating process can be smoothly performed when the polymer solid electrolyte forming solution is applied to a substrate. For example, the concentration of the polymer solution containing a crosslinkable functional group may be 5% to 20%, specifically, 5% or more, 7% or more, or 9% or more, and 13% or less, 17% or less, or 20% or less. If the concentration of the polymer solution containing a crosslinkable functional group is less than 5%, the concentration is too dilute and may run off when applied to a substrate, and if it exceeds 20%, it may be difficult to dissolve a lithium salt at a desired concentration in the polymer solution and may be difficult to apply in the form of a uniform thin film due to high viscosity.
[0073] In one embodiment of the present invention, in the step (S2), the polymer solid electrolyte forming solution may be coated on a substrate to form a coating film.
[0074] The substrate is not particularly limited as long as it can serve as a support on which the polymer solid electrolyte forming solution is applied, and may be, for example, stainless steel (SS), a polyethylene terephthalate film, a polytetrafluoroethylene film, a polyethylene film, a polypropylene film, a polybutene film, a polybutadiene film, a vinyl chloride copolymer film, a polyurethane film, an ethylene-vinyl acetate film, an ethylene-propylene copolymer film, an ethylene-ethyl acrylate copolymer film, an ethylene-methyl acrylate copolymer film, or a polyimide film.
[0075] The coating method is also not particularly limited as long as it can coat the polymer solid electrolyte solution on the substrate in the form of a film, and may be, for example, bar coating, roll coating, spin coating, slit coating, die coating, blade coating, comma coating, slot die coating, lip coating, or solution casting.
[0076] In one embodiment of the present invention, in the step (S3), the coating film is frozen and thawed to form a polymer cross-linked structure including the cross-linkable functional group, and the polymer cross-linked structure may produce a first polymer solid electrolyte including the first lithium salt and the first solvent.
[0077] In the freezing process, the polymer and water contained in the aqueous polymer solution containing cross-linkable functional groups used to form the coating film may undergo phase separation. The phase separation may be induced because the strength of the hydrogen bonds between the cross-linkable functional groups and the water molecules is stronger than that between the cross-linkable functional groups and the water molecules. The water molecules aggregated by the hydrogen bonds with the water molecules exist in an icy state (ice phase) through the freezing process. As a result, the number of cross-linkable functional groups that form hydrogen bonds through interaction with the water molecules is significantly reduced.
[0078] Due to the phase separation, the inside of the coating film is divided into (i) a polymer-poor phase and (ii) a polymer-rich phase.
[0079] The (i) polymer-poor phase is a portion that contains water molecules that are aggregated by hydrogen bonds with water molecules, and exists in an icy state (ice phase), which can also be called a free water state.
[0080] The (ii) polymer-rich phase is a portion containing a polymer that has been phase-separated from water. The phase-separated polymer is a polymer containing a cross-linking functional group that has been freed from interactions with water molecules, and after phase separation, it is in a free state and does not form crystals through regular folding, but exists in an amorphous state with relatively free behavior, which is called an amorphous polymer chain.
[0081] In addition, some of the cross-linkable functional groups contained in the phase-separated polymer form localized crystallites, which act as cross-linkable junction points to form a cross-linked structure including the bonds (a), (b), and (c).
[0082] In addition, in the thawing process after the freezing process, the ice contained in the (i) polymer-poor phase melts and evaporates, thereby producing a polymer solid electrolyte with an increased free volume.
[0083] The freezing can be performed by appropriately selecting conditions that can freeze the coating film. For example, the freezing temperature can be -30°C to -10°C, and specifically, the freezing temperature can be -30°C or higher, -25°C or higher, or -23°C or higher, and can be -18°C or lower, -15°C or lower, or -10°C or lower. If the freezing temperature is lower than -30°C, cracks may occur in the coating film, and if it exceeds -10°C, phase separation between the polymer and water may not be sufficient, making it difficult to form an amorphous polymer chain region. The freezing can be performed by taking into consideration the time required for sufficient freezing within a range of 20 hours to 30 hours.
[0084] The thawing can be performed by appropriately selecting conditions that allow the frozen coating film to be thawed to an extent that it can be used as a polymer solid electrolyte. For example, the thawing temperature may be 15°C to 35°C, or may be room temperature (25°C). If the thawing temperature is less than 15°C, the efficiency of drying water after thawing (ice melting) may decrease, and if it exceeds 35°C, the coating film may shrink and wrinkle or warp may occur.
[0085] As described above, the freezing and thawing process induces the bonds of (a), (b) and (c) to form cross-linked structures and amorphous polymer chains.
[0086] Therefore, the degree of formation of the cross-linked structure can be adjusted by the number of times the freezing and thawing processes are performed. When the process of performing the freezing process followed by the thawing process is defined as one cycle, the freezing and thawing processes can be performed one or more cycles, two or more cycles, three or more cycles, or five or more cycles. The upper limit of the cycle is not particularly limited, and may be 10 or less cycles, 13 or less cycles, or 15 or less cycles. As the number of cycles of the freezing and thawing processes increases within the above range, the more cross-linked structures can be formed, and thus the modulus and strength of the polymer solid electrolyte can be increased.
[0087] In one embodiment of the present invention, in the step (S4), the first solvent in the first polymer solid electrolyte may be replaced with a solution containing a second lithium salt and a second solvent to prepare a second polymer solid electrolyte.
[0088] The first solvent, the second solvent, and the second lithium salt are as described above.
[0089] The solvent exchange means removing the first solvent in the first polymer solid electrolyte and exchanging it so that the second lithium salt and the second solvent are mostly present. By the solvent exchange, a second polymer solid electrolyte including the second lithium salt and the second solvent can be produced.
[0090] The solvent exchange may be performed by drying the first solvent contained in the first polymer solid electrolyte at a high temperature, and then immersing the electrolyte in a solution containing the second lithium salt and the second solvent to exchange the first solvent with the second solvent. More specifically, the first polymer solid electrolyte containing the first solvent is placed in a vacuum oven, dried at a low temperature (50°C) for 6 hours, and then dried at a high temperature (100°C) for 12 hours. The first solid electrolyte dried in a dry room environment is then immersed in a solution containing the second lithium salt and the second solvent at room temperature for 24 hours to exchange the first solvent with the second solvent.
[0091] all solid state battery The present invention also relates to an all-solid-state battery including the polymer solid electrolyte, the all-solid-state battery including a negative electrode, a positive electrode, and a polymer solid electrolyte interposed between the negative electrode and the positive electrode, the solid electrolyte having the above-mentioned characteristics.
[0092] Specifically, the polymer solid electrolyte is suitable as an electrolyte for an all-solid-state battery because the crystallinity is reduced by the formation of physical cross-links through a freezing and thawing process, and the ionic conductivity is improved through a solvent exchange process.
[0093] In the present invention, the positive electrode included in the all-solid-state battery may include a positive electrode active material layer, and the positive electrode active material layer may be formed on one surface of a positive electrode current collector.
[0094] The positive electrode active material layer includes a positive electrode active material, a binder, and a conductive material.
[0095] The positive electrode active material is not particularly limited as long as it is a material capable of reversibly absorbing and releasing lithium ions. Examples of the positive electrode active material include lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), Li[Ni x Co y Mn z M v ]O2 (wherein M is any one or more elements selected from the group consisting of Al, Ga, and In; 0.3≦x<1.0, 0≦y, z≦0.5, 0≦v≦0.1, and x+y+z+v=1), Li (Li a M b-a-b’ M' b’ )O 2-c A c (wherein, 0≦a≦0.2, 0.6≦b≦1, 0≦b'≦0.2, 0≦c≦0.2; M includes Mn and at least one selected from the group consisting of Ni, Co, Fe, Cr, V, Cu, Zn, and Ti; M' is at least one selected from the group consisting of Al, Mg, and B; and A is at least one selected from the group consisting of P, F, S, and N); 1+y Mn2-y Lithium manganese oxides such as LiMnO4 (where y is 0-0.33), LiMnO3, LiMn2O3, LiMnO2; lithium copper oxide (Li2CuO2); vanadium oxides such as LiV3O8, LiFe3O4, V2O5, Cu2V2O7; and the chemical formula LiNi 1-y Ni-site type lithium nickel oxide represented by MyO2 (where M=Co, Mn, Al, Cu, Fe, Mg, B or Ga, and y=0.01-0.3); chemical formula LiMn 2-y M y Examples of such compounds include, but are not limited to, lithium manganese composite oxides expressed as Li2Mn3MO8 (where M=Co, Ni, Fe, Cr, Zn, or Ta, and y=0.01-0.1) or Li2Mn3MO8 (where M=Fe, Co, Ni, Cu, or Zn); LiMn2O4 in which part of the Li in the chemical formula is replaced with an alkaline earth metal ion; disulfide compounds; and Fe2(MoO4)3.
[0096] In addition, the positive electrode active material may be included in an amount of 40 to 80 wt % based on the total weight of the positive electrode active material layer. Specifically, the content of the positive electrode active material may be 40 wt % or more or 50 wt % or more, and 70 wt % or less or 80 wt % or less. If the content of the positive electrode active material is less than 40 wt %, the connectivity between the wet positive electrode active material layer and the dry positive electrode active material layer may be insufficient, and if it exceeds 80 wt %, the mass transfer resistance may be large.
[0097] The binder is a component that aids in bonding the positive electrode active material to the conductive material and the current collector, and is preferably a rubber such as styrene-butadiene rubber, acrylated styrene-butadiene rubber, acrylonitrile copolymer, acrylonitrile-butadiene rubber, nitrile butadiene rubber, acrylonitrile-styrene-butadiene copolymer, acrylic rubber, butyl rubber, fluororubber, polytetrafluoroethylene, polyethylene, polypropylene, ethylene / propylene copolymer, polybutadiene, polyethylene oxide, chlorosulfonated polyethylene, polyvinylpyrrolidone, polyvinylpyridine, polyvinyl alcohol, polyvinyl acetate, polyepichlorohydrin, polyphosphazene, polyacrylonitrile, polybutadiene ... The binder may include at least one selected from the group consisting of styrene-butadiene rubber, polytetrafluoroethylene, carboxymethylcellulose, polystyrene, latex, acrylic resin, phenolic resin, epoxy resin, carboxymethylcellulose, hydroxypropylcellulose, cellulose acetate, cellulose acetate butyrate, cellulose acetate propionate, cyanoethylcellulose, cyanoethylsucrose, polyester, polyamide, polyether, polyimide, polycarboxylate, polycarboxylic acid, polyacrylic acid, polyacrylate, lithium polyacrylate, polymethacrylic acid, polymethacrylate, polyacrylamide, polyurethane, polyvinylidene fluoride, and poly(vinylidene fluoride)-hexafluoropropene. Preferably, the binder may include at least one selected from the group consisting of styrene-butadiene rubber, polytetrafluoroethylene, carboxymethylcellulose, polyacrylic acid, lithium polyacrylate, and polyvinylidene fluoride.
[0098] In addition, the binder may be included in an amount of 1 wt% to 30 wt% based on the total weight of the positive electrode active material layer, and specifically, the content of the binder may be 1 wt% or more or 3 wt% or more, and 15 wt% or less or 30 wt% or less. If the content of the binder is less than 1 wt%, the adhesive strength between the positive electrode active material and the positive electrode current collector may decrease, and if it exceeds 30 wt%, the adhesive strength is improved, but the content of the positive electrode active material may decrease accordingly, and the battery capacity may decrease.
[0099] The conductive material is not particularly limited as long as it prevents side reactions in the internal environment of the all-solid-state battery, does not induce chemical changes in the battery, and has excellent electrical conductivity. Representative examples include graphite or conductive carbon. Examples of the conductive material include graphite such as natural graphite and artificial graphite; carbon black, acetylene black, ketjen black, denka black, thermal black, channel black, furnace black, lamp black, summer black, and other carbon blacks; carbon-based substances having a graphene or graphite crystal structure; conductive fibers such as carbon fibers and metal fibers; carbon fluoride; metal powders such as aluminum powder and nickel powder; conductive whiskers such as zinc oxide and potassium titanate; conductive oxides such as titanium oxide; and conductive polymers such as polyphenylene derivatives. These may be used alone or in combination of two or more kinds, but are not necessarily limited thereto.
[0100] The conductive material may be included in an amount of 0.5 wt% to 30 wt% based on the total weight of the positive electrode active material layer, and specifically, the content of the conductive material may be 0.5 wt% or more or 1 wt% or more, and 20 wt% or less or 30 wt% or less. If the content of the conductive material is less than 0.5 wt%, it may be difficult to expect an improvement in electrical conductivity or the electrochemical properties of the battery may be deteriorated, and if the content is more than 30 wt%, the amount of the positive electrode active material may be relatively small, and the capacity and energy density may be reduced. The method of including the conductive material in the positive electrode is not significantly limited, and a conventional method known in the art, such as coating on the positive electrode active material, may be used.
[0101] The positive electrode current collector supports the positive electrode active material layer and transfers electrons between an external conductor and the positive electrode active material layer.
[0102] The positive electrode current collector is not particularly limited as long as it does not induce chemical changes in the all-solid-state battery and has high electronic conductivity. For example, the positive electrode current collector may be made of copper, stainless steel, aluminum, nickel, titanium, palladium, baked carbon, copper or stainless steel surface-treated with carbon, nickel, silver, or the like, or an aluminum-cadmium alloy.
[0103] The positive electrode current collector may have a fine uneven structure on the surface thereof or a three-dimensional porous structure in order to strengthen the bonding force with the positive electrode active material layer, and may include various forms such as a film, sheet, foil, mesh, net, porous body, foam, nonwoven fabric, etc.
[0104] The positive electrode may be prepared according to a conventional method, specifically, by mixing a positive electrode active material, a conductive material, and a binder in an organic solvent to prepare a composition for forming a positive electrode active material layer, coating the composition on a positive electrode current collector, drying the composition, and optionally compressing the composition into a current collector to improve the electrode density. In this case, it is preferable to use an organic solvent that can uniformly disperse the positive electrode active material, the binder, and the conductive material and that can be easily evaporated. Specifically, acetonitrile, methanol, ethanol, tetrahydrofuran, water, isopropyl alcohol, etc. may be used.
[0105] In the present invention, the negative electrode included in the all-solid-state battery may include a negative electrode active material layer, and the negative electrode active material layer may be formed on one surface of a negative electrode current collector.
[0106] The negative electrode active material may include a material capable of reversibly intercalating or deintercalating lithium (Li+), a material capable of reversibly forming a lithium-containing compound by reacting with lithium ions, lithium metal, or a lithium alloy.
[0107] The material capable of reversibly inserting or deintercalating the lithium ion (Li+) may be, for example, crystalline carbon, amorphous carbon, or a mixture thereof. The material capable of reacting with the lithium ion (Li+) to reversibly form a lithium-containing compound may be, for example, tin oxide, titanium nitrate, or silicon. The lithium alloy may be, for example, an alloy of lithium (Li) and a metal selected from the group consisting of sodium (Na), potassium (K), rubidium (Rb), cesium (Cs), francium (Fr), beryllium (Be), magnesium (Mg), calcium (Ca), strontium (Sr), barium (Ba), radium (Ra), aluminum (Al), and tin (Sn).
[0108] Preferably, the negative electrode active material is lithium metal, specifically, in the form of a lithium metal thin film or lithium metal powder.
[0109] The negative electrode active material may be included in an amount of 40 to 80 wt % based on the total weight of the negative electrode active material layer. Specifically, the content of the negative electrode active material may be 40 wt % or more or 50 wt % or more, or 70 wt % or less or 80 wt % or less. If the content of the negative electrode active material is less than 40 wt %, the connectivity between the wet negative electrode active material layer and the dry negative electrode active material layer may be insufficient, and if it exceeds 80 wt %, the mass transfer resistance may be large.
[0110] The binder is the same as that described above in the positive electrode active material layer.
[0111] The conductive material is the same as that described above in the positive electrode active material layer.
[0112] The negative electrode current collector is not particularly limited as long as it does not induce a chemical change in the battery and has conductivity, and for example, the negative electrode current collector can be made of copper, stainless steel, aluminum, nickel, titanium, baked carbon, copper or stainless steel surface-treated with carbon, nickel, titanium, silver, etc., aluminum-cadmium alloy, etc. Similarly to the positive electrode current collector, the negative electrode current collector can be in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc., having fine irregularities formed on the surface.
[0113] The method for manufacturing the negative electrode is not particularly limited, and the negative electrode may be manufactured by forming a negative electrode active material layer on a negative electrode current collector using a method for forming a layer or film commonly used in the art. For example, methods such as compression bonding, coating, deposition, etc. may be used. In addition, the negative electrode of the present invention also includes a case where a thin metallic lithium film is formed on a metal plate by initial charging after assembling a battery without a thin lithium film on the negative electrode current collector.
[0114] The present invention also provides a battery module including the all-solid-state battery as a unit cell, a battery pack including the battery module, and a device including the battery pack as a power source.
[0115] Specific examples of the device include, but are not limited to, power tools that are driven by a battery-type motor; electric vehicles, including electric vehicles (EV), hybrid electric vehicles (HEV), plug-in hybrid electric vehicles (PHEV), etc.; electric two-wheeled vehicles, including electric bicycles (E-bikes) and electric scooters (E-scooters); electric golf carts; power storage systems, etc. Preferred examples are shown below to aid in the understanding of the present invention. However, the following examples are merely illustrative of the present invention, and it is obvious to those skilled in the art that various changes and modifications are possible within the scope of the scope and technical ideas of the present invention, and such changes and modifications naturally fall within the scope of the accompanying claims.
[0116] Preferred examples are shown below to aid in understanding the present invention. The following examples are provided to facilitate understanding of the present invention, and the present invention is not limited thereto.
[0117] In the following examples and comparative examples, polymer solid electrolytes were prepared that contained a polymer having a crosslinkable functional group, a lithium salt, and a solvent as shown in Table 1 below.
[0118] [Table 1]
[0119] Working Example Example 1: Preparation of polymer solid electrolyte (1) Production of polymer solid electrolytes PVA (Mw: 89,000 g / mol; degree of hydrolysis: >99%) was mixed with water to prepare a 10% PVA aqueous solution. LiTFSI was added to the PVA aqueous solution and stirred to prepare a solution containing PVA, which is a polymer having a cross-linking functional group, and LiTFSI, which is a first lithium salt. At this time, the molar ratio ([Li] / [O]) of “O” contained in the cross-linking functional group of the PVA to “Li” contained in the lithium salt was set to 0.4.
[0120] The solution was applied onto a substrate (SS foil) by bar coating, and then frozen at -20°C for 24 hours and thawed at 25°C to induce physical cross-linking of the polymer, thereby preparing a polymer solid electrolyte.
[0121] After removing the first solvent, water (HO), from the inside of the prepared polymer solid electrolyte, a solution containing 1M LiPF as a second lithium salt and ethyl methyl carbonate (EMC) as a second solvent was added to prepare a solvent-exchanged polymer solid electrolyte.
[0122] Example 2 A polymer solid electrolyte was prepared in the same manner as in Example 1, except that the second solvent was DMC.
[0123] Example 3 A polymer solid electrolyte was prepared in the same manner as in Example 1, except that the molar ratio ([Li] / [O]) of “O” contained in the cross-linking functional group of the PVA to “Li” contained in the lithium salt was 0.25, and the first solvent was DMSO.
[0124] Comparative Example Comparative Example 1 A polymer solid electrolyte was prepared in the same manner as in Example 1, except that the first solvent, water (HO), in the prepared polymer solid electrolyte was removed, and then a solution containing a second solvent, ethyl methyl carbonate (EMC), was added to exchange the solvent.
[0125] Comparative Example 2 A polymer solid electrolyte was prepared in the same manner as in Example 1, except that a solution containing PVA, a polymer having a cross-linkable functional group, and LiTFSI, a lithium salt, was coated on a SS foil, a substrate, and then dried at 80° C. without freezing and thawing processes.
[0126] Comparative Example 3 A polymer solid electrolyte was prepared in the same manner as in Example 1, except that a solution containing PVA, a polymer having a cross-linkable functional group, and LiTFSI, a lithium salt, was coated on a SS foil, a substrate, and then dried at 25° C. without a freezing and thawing process.
[0127] Comparative Example 4 A polymer solid electrolyte was prepared in the same manner as in Comparative Example 1, except that a PEO polymer was used instead of PVA and the PEO polymer was dissolved in acetonitrile.
[0128] Comparative Example 5 A polymer solid electrolyte was prepared in the same manner as in Example 1, except that PEO polymer was used instead of PVA.
[0129] Experimental Example Experimental Example 1 The ionic conductivity of the film-type polymer solid electrolyte prepared in the Examples and Comparative Examples was measured using a 1.7671 cm 2 The solid polymer electrolyte was punched out into a circle of a desired size, and the punched solid polymer electrolyte was placed between two pieces of stainless steel (SS) to prepare a coin cell.
[0130] Resistance was measured using an electrochemical impedance spectrometer (EIS, VM3, Bio Logic Science Instrument) at 25° C., an amplitude of 10 mV, and a scan range of 500 kHz to 20 MHz, and then the ionic conductivity of the polymer solid electrolyte was calculated using the following Equation 2.
[0131] [Formula 2]
number
[0132] In the above formula 2, σ i is the ionic conductivity (S / cm) of the polymer solid electrolyte, R is the resistance (Ω) of the polymer solid electrolyte measured by the electrochemical impedance spectrometer, L is the thickness (μm) of the polymer solid electrolyte, and A is the area (cm 2 )
[0133] The ionic conductivity of the polymer solid electrolyte calculated using Equation 2, whether a freestanding film could be formed, and the results of observing the appearance of the polymer solid electrolyte are shown in Table 2. At this time, whether the freestanding film could be formed (formed: O, not formed: X) and the appearance of the polymer solid electrolyte were observed with the naked eye.
[0134] [Table 2]
[0135] As shown in Table 2, it was confirmed that a polymer solid electrolyte in the form of a free-standing film can be prepared by using PVA having an appropriate range of crosslinkable functional group and lithium molar ratio ([Li] / [OH]) of the lithium salt as the polymer containing the crosslinkable functional group and applying a freezing and thawing process (Examples 1 to 3).
[0136] Comparing the ionic conductivity of the polymer solid electrolytes of Example 1 and Comparative Example 1, it was confirmed that the polymer solid electrolyte of Example 1 containing the second solvent and the second lithium salt had a higher ionic conductivity. Therefore, it was found that the solvent exchange using a solution containing the second lithium salt in addition to the second solvent during the solvent exchange process showed better ionic conductivity.
[0137] Comparative Example 2 is an electrolyte prepared using a high-temperature drying process at 80°C. Not only was it impossible to form a network, but it was also difficult to form a uniform film, making it impossible to measure the ion conductivity. Comparative Example 3 is an electrolyte prepared using a room-temperature drying process at 25°C. Due to the absence of physical crosslinks formed by the freezing and thawing processes, the mechanical strength of the polymer solid electrolyte was low, and the ion conductivity was also low.
[0138] In Comparative Examples 4 and 5, PEO was used as the polymer, but even when the freezing and thawing process was applied, a cross-linked structure was not formed, and the ionic conductivity was significantly low.
[0139] Example 4 A polymer solid electrolyte was prepared in the same manner as in Example 1, except that the freezing and thawing process was performed twice.
[0140] Example 5 A polymer solid electrolyte was prepared in the same manner as in Example 1, except that one cycle of freezing and thawing was performed.
[0141] Example 6 A polymer solid electrolyte was prepared in the same manner as in Example 1, except that the freezing and thawing process was performed five times.
[0142] Example 7 A polymer solid electrolyte was prepared in the same manner as in Example 1, except that the freezing and thawing process was performed 10 cycles.
[0143] Comparative Example 6 PVA (Mw: 89,000 g / mol; degree of hydrolysis: >99%) was mixed with water to prepare a 10 wt% PVA aqueous solution, which was then coated on SS foil and dried at high temperature (90°C, 3 hours) to prepare a PVA film.
[0144] Comparative Example 7 A PVA film was prepared in the same manner as in Comparative Example 6, except that boric acid was added as a crosslinking agent.
[0145] Experimental Example 2 An experiment was carried out to compare the presence or absence of a cross-linked structure formed inside the polymer solid electrolyte and the degree of its formation.
[0146] Since the purpose of the present study was to compare only the presence or absence and the degree of formation of a crosslinked structure, the PVA film of Comparative Example 6, which did not contain a crosslinked structure, and the PVA film of Comparative Example 7, in which a chemical crosslinked structure was formed by a crosslinking agent, were used for comparison.
[0147] (1) Check the degree of swelling The test samples were immersed in water at room temperature (25° C.) for 12 hours, and the degree of swelling of the samples was checked and judged according to the following criteria.
[0148] <Criteria for determining the degree of swelling> ◎: Swelled to 80% or more of the total volume. ○: Swelled to 50% or more of the total volume. △: Swelling of 20% or more of the total volume. X: Swelling of less than 10% of the total volume.
[0149] (2) Elastic modulus The elastic modulus was measured by a Universal testing machine (UTM).
[0150] [Table 3]
[0151] Referring to Table 3, Examples 1 and 4 to 7 show a certain level or more of elastic modulus as the polymer solid electrolyte prepared by the freezing and thawing process, and as the number of cycles of the freezing and thawing process increases, the elastic modulus also increases. In addition, as the number of cycles increases, the degree of swelling also decreases. In general, the degree of swelling and mechanical properties of a polymer are greatly affected by the degree of crosslinking. The formation of crosslinking points increases the internal resistance of the polymer chain, thereby inducing an increase in swelling resistance and mechanical strength. In particular, the formation of physical crosslinks based on the freezing-thawing process is affected by the number of repetitions of the freezing-thawing process. As the number of cycles increases, the elastic modulus increases and the degree of swelling decreases, so it can be seen that as the number of cycles increases, the crosslinked structure also increases. Even though Example 5 shows that the degree of swelling is 50% or more of the total volume, this is a result measured after 12 hours at room temperature, and is suitable for the properties required for a polymer solid electrolyte for an all-solid-state battery.
[0152] It is seen that the PVA film of Comparative Example 6 is swollen to 80% or more of its total volume, which indicates that no cross-linked bond structure is present inside the polymer.
[0153] The PVA film of Comparative Example 7 had a chemical cross-linked structure formed by the addition of boric acid as a cross-linking agent, and it was shown that the elastic modulus was reduced compared to Comparative Example 6, in which no cross-linked structure was formed.
[0154] The PVA film of Comparative Example 7 had a reduced elastic modulus compared to that of Comparative Example 6 due to the formation of a chemical cross-linked structure, reduced crystallinity, and increased polymer flexibility.
[0155] Meanwhile, Examples 1 and 4 to 7 correspond to PVA films in the form of hydrogels based on physical cross-linking formed using a freezing and thawing process, unlike the manufacturing methods of Comparative Examples 6 and 7. This shows a tendency for the modulus of elasticity to increase as the cross-linking increases. In Examples 1 and 4 to 7, as the number of freezing and thawing process cycles increases, the cross-linked structure also increases, and the modulus of elasticity also tends to increase. Through the freezing and thawing process, some of the cross-linking functional groups contained in the PVA form localized crystallites, and the localized crystallites act as cross-linkable junction points, increasing the modulus of elasticity.
[0156] Although the present invention has been described above using limited examples and drawings, the present invention is not limited thereto, and it goes without saying that various modifications and variations can be made by a person having ordinary knowledge in the technical field to which the present invention pertains within the technical spirit of the present invention and the equivalent scope of the claims described below.
Claims
1. a polymer solid electrolyte comprising: a polymer including a cross-linkable functional group; a lithium salt including a first lithium salt and a second lithium salt; and a solvent including a first solvent and a second solvent; The polymer solid electrolyte comprises an amorphous polymer chain having a cross-linked structure and the cross-linkable functional group, the cross-linked structure includes (a) a cross-link between the cross-linkable functional groups, (b) a cross-link between the cross-linkable functional groups and the first solvent, and (c) a bond between the cross-linkable functional groups and the first lithium salt.
2. the (a) cross-linking bond between the cross-linkable functional groups includes a hydrogen bond, the cross-linking between the cross-linkable functional group and the first solvent (b) comprises a hydrogen bond; 2. The polymer solid electrolyte according to claim 1, wherein the bond between the cross-linkable functional group and the first lithium salt (c) includes a bond formed by Lewis acid-base interaction.
3. The polymer solid electrolyte according to claim 1, wherein the content of the first solvent is 1 to 1000 ppm.
4. 2. The polymer solid electrolyte according to claim 1, wherein the first solvent comprises at least one selected from the group consisting of water, ethanol, isopropyl alcohol, dimethyl sulfoxide, acetonitrile, NMP, a co-solvent obtained by mixing water and alcohol, and a co-solvent obtained by mixing water and dimethyl sulfoxide.
5. The second solvent includes at least one selected from the group consisting of ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), ethylene carbonate (EC), propylene carbonate (PC), vinylene carbonate (VC), diethyl carbonate (DEC), methyl ethyl carbonate (MEC), tetrahydrofuran (THF), 2-methyltetrahydrofuran (2-MeTHF), dioxolane (DOX), dimethoxyethane (DME), diethoxyethane (DEE), γ-butyrolactone (GBL), acetonitrile (AN), and sulfolane. The polymer solid electrolyte according to claim 1.
6. 2. The polymer solid electrolyte according to claim 1, wherein the cross-linkable functional group comprises at least one selected from the group consisting of a hydroxyl group, a carboxyl group, and an amide group.
7. The polymers containing the crosslinkable functional groups include polyvinyl alcohol (PVA), gelatin, methylcellulose, agar, dextrin, poly(vinyl pyrrolidone), poly(acrylamide), starch-carboxymethyl cellulose, hyaluronic acid-methyl cellulose, and the like. The polymer solid electrolyte according to claim 1, which comprises at least one selected from the group consisting of N-isopropylacrylamide, N-isopropylacrylamide, chitosan, poly(N-isopropylacrylamide), and amino-terminated polyethylene glycol.
8. The first lithium salt and the second lithium salt are the same or different, and each independently represents (CF 3 SO 2 ) 2 NLi (Lithium bis(trifluoromethanesulfonyl)imide, LiTFSI), (FSO 2 ) 2 NLi (Lithium bis(fluorosulfonyl)imide, LiFSI), LiNO 3 , LiOH, LiCl, LiBr, LiI, LiClO 4 , LiBF 4 , LiB 10 C 10 , LiPF 6 , LiCF 3 SO 3 , LiCF 3 CO 2 , LiAsF 6 , LiSbF 6 , LiAlCl 4 , C.H. 3 SO 3 Li, C.F. 3 SO 3 Li, LiSCN and LiC(CF 3 SO 2 ) 3 The polymer solid electrolyte according to claim 1, comprising one or more selected from the group consisting of:
9. 2. The polymer solid electrolyte according to claim 1, wherein the molar ratio ([Li] / [G]) of the lithium ([Li]) of the lithium salt to the cross-linking functional group ([G]) of the polymer is greater than 0.1 and less than 0.
5.
10. 2. The polymer solid electrolyte of claim 1, comprising exchanging a first solvent in the polymer solid electrolyte with a solution comprising a second lithium salt and a second solvent.
11. 2. The polymer solid electrolyte according to claim 1, wherein the concentration of the second lithium salt is 0.5M to 1.2M.
12. The polymer solid electrolyte of claim 1 , wherein the polymer solid electrolyte is in the form of a freestanding film or a coating layer.
13. The ionic conductivity of the polymer solid electrolyte is 1.0×10 -4 The polymer solid electrolyte according to claim 1, wherein the specific surface area is 100 nm or more.
14. (S1) adding a first lithium salt to a solution including a polymer having a cross-linkable functional group and a first solvent to prepare a polymer solid electrolyte forming solution; (S2) applying the polymer solid electrolyte forming solution onto a substrate to form a coating film; (S3) freezing and thawing the coating film to form a polymer cross-linked structure including the cross-linkable functional group, the polymer cross-linked structure including the first lithium salt and the first solvent, to prepare a first polymer solid electrolyte; (S4) exchanging the first solvent in the first polymer solid electrolyte with a solution containing a second lithium salt and a second solvent to prepare a second polymer solid electrolyte; A method for producing a polymer solid electrolyte.
15. The polymer solid electrolyte includes a cross-linked structure, the cross-linked structure includes: (a) a cross-link between the cross-linking functional groups; (b) a cross-link between the cross-linking functional groups and the first solvent; and (c) a bond between the cross-linking functional groups and the first lithium salt; the (a) cross-linking bond between the cross-linkable functional groups includes a hydrogen bond, the cross-linking between the cross-linkable functional group and the first solvent (b) comprises a hydrogen bond; The method for producing a polymer solid electrolyte according to claim 14, wherein the bond between the cross-linkable functional group and the first lithium salt (c) includes a bond due to Lewis acid-base interaction.
16. The method for producing a polymer solid electrolyte according to claim 14, wherein the freezing is carried out at −30° C. to −10° C.
17. The method for producing a polymer solid electrolyte according to claim 14, wherein the thawing is carried out at 15°C to 35°C.
18. 15. The method for producing a polymer solid electrolyte according to claim 14, wherein the solvent exchange is performed by drying a first solvent contained in a first polymer solid electrolyte at a high temperature and then immersing the first polymer solid electrolyte in a solution containing the second lithium salt and a second solvent to exchange the first solvent for the second solvent.
19. An all-solid-state battery comprising the polymer solid electrolyte according to any one of claims 1 to 13.
Citation Information
Patent Citations
Gel electrolyte
JP1994150940A
Nonaqueous electrolyte secondary battery and method for manufacturing positive electrode for the secondary battery
JP2014026777A
Composite particle for lithium ion secondary battery negative electrode, method for producing the same, negative electrode for lithium ion secondary battery, and lithium ion secondary battery
JP2014029848A
Power storage element
JP2014032955A
Solid-state polymer electrolyte membrane with grid structure, and preparation method thereof
CN112259788A